Analisis Potensi Pengembangan Destinasi Wisata Pelabuhan Rambang Kota Palangka Raya - Jajae, Jajae; Hukom, Alexandra (STAI Denpasar Bali, 2023)
The purpose of the study of Rambang Palangka Raya Port using SWOT analysis is to identify internal and external factors that can influence the development of the tourism potential of Rambang Port. The survey method is a qualitative approach using the SWOT analysis tool. Overall, the Internal Factor Analysis (IFAS) and External Factor Analysis (EFAS) show that Lambang Harbor has great potential for tourism development. However, several elements still need to be improved so that this tourist destination can develop better. Appropriate strategies must be implemented to overcome weaknesses and take advantage of existing opportunities to promote regional tourism development. Lanbang Port is expected to become an attractive and popular tourist destination. Research can be carried out to support the development of Lambang Port tourism. Studying tourist preferences will help determine the factors that influence tourist decisions in choosing this natural tourism destination, as well as help determine the type and size of facilities most needed to optimize local tourism management. Research on marketing and promotion strategies can help increase tourist visits to Rambang Harbor by identifying more specific tourist preferences and needs.